Mathematics Communication Ability In Mathematics Learning - Halawati, Firda; Laelasari, Dian (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
The problem that is the focus of this research is the decline in students' mathematical communication skills in learning mathematics at MI PUI Ciawigebang. The aims of this study were to: 1) determine the mathematical communication skills of students; 2) Knowing the mathematics learning of students; 3) Knowing students' mathematical communication skills in learning mathematics. The type of research used is descriptive qualitative research. The source of data used in this study is a primary source, namely the results of interviews with 6 research subjects taken based on 3 abilities, namely 2 students with high abilities, 2 students with moderate abilities, and 2 students with low abilities. and secondary sources in the form of journals and books. The research instrument used in this study was a mathematical communication ability test, documentation, and interviews. The research subjects were fifth grade students at MI PUI Ciawigebang Kab. Brass. Based on the results of research and discussions that have been carried out, some conclusions can be drawn as follows. 1) Mathematical communication skills in class V MI PUI Ciawigebang are based on written mathematical communication skills and Oral mathematical communication skills, each of which consists of 3 aspects of mathematical communication skills. mathematical communication skills in class V MI PUI Ciawigebang only reached Aspect 2; .2) Mathematics learning for class V MI PUI Ciawigebang based on the grouping of High, medium, and low categories is still not optimal, this is due to the lack of confidence in students in presenting mathematical ideas in writing and orally on the given problems; 3) students' mathematical communication skills in learning mathematics. Subjects in the high category capable in all 3 aspects can demonstrate the use of mathematical language and forms of mathematical representation. Subjects in the moderate category in aspects 1 and 2 can write down information that is known and asked in full, while low category subjects are only able in aspect 1 to be able to express ideas through writing and demonstrate and visually describe